From Agricultural Research to 'Product Development': What Role for User Feedback and Feedback Loops? - Sumberg, J.; Heirman, J.; Raboanarielina, C.; Kaboré, A. (SAGE Publications, 2013)
Agricultural research for development (AR4D) is often discussed in terms of abandoning 'business as usual'. One important element of the reframing of agricultural research is an emphasis on the development of useful 'products', which immediately brings 'users' to centre stage. In this paper the authors review the literature on user involvement from the field of new product development (NPD). They then propose a conceptual model of feedback and feedback loops within AR4D and use this model to analyse examples of feedback generation in rice research in West Africa. On the basis of this initial analysis they conclude that, while there are many ongoing activities that could potentially provide useful feedback, in the majority of cases this potential is probably not being realized. Unless feedback is approached much more systematically, the promise of AR4D as a means of generating useful products for farmers and others will probably remain unfulfilled.